2007
DOI: 10.1128/cvi.00409-06
|View full text |Cite
|
Sign up to set email alerts
|

OspC Phylogenetic Analyses Support the Feasibility of a Broadly Protective Polyvalent Chimeric Lyme Disease Vaccine

Abstract: Using available Borrelia outer surface protein C (OspC) sequences, a phylogenetic analysis was undertaken to delineate the number of antigenic domains required for inclusion in a broadly protective, chimeric, OspC-based Lyme disease vaccine. The data indicate that approximately 34 would be required and that an OspC-based vaccinogen is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 51 publications
2
51
1
2
Order By: Relevance
“…This possibility contradicts findings of other investigators who have identified multiple epitopes within hypervariable regions of OspC that also induce complement-fixing antibodies (3,(8)(9)(10)(11), indicating that a multivalent vaccine will be necessary for comprehensive protection. In fact, Earnhart and Marconi (11) showed that broad protection required at least 8 OspC borreliacidal antibody epitopes.…”
contrasting
confidence: 55%
“…This possibility contradicts findings of other investigators who have identified multiple epitopes within hypervariable regions of OspC that also induce complement-fixing antibodies (3,(8)(9)(10)(11), indicating that a multivalent vaccine will be necessary for comprehensive protection. In fact, Earnhart and Marconi (11) showed that broad protection required at least 8 OspC borreliacidal antibody epitopes.…”
contrasting
confidence: 55%
“…Many OspC "types" (allelic variants) have been described in the literature (14,35,36), some having been associated with a greater propensity for dissemination of the bacteria from the site of initial infection following the tick bite. While the association of OspC type and disseminated disease is beyond the scope of this study, to be effective within the constraints of a diagnostic assay, an epitope must be highly conserved.…”
Section: Resultsmentioning
confidence: 99%
“…S1 in the supplemental material). Sequences for each OspC type were identified previously (14,35,36) ELISA. Maxisorp (Nunc, Rochester, NY) 96-well plates were coated with 10 g/ml of peptide in 0.1 M sodium carbonate buffer, pH 9.4, for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Although this argument was sidestepped with claims that blood from the vaccinated host killed the OspA-expressing Borrelia in the midgut of the ticks (51), we now know that the saliva of ticks can inactivate complement (101,121), eliminating the threat of complementdependent OspA bactericidal antibody. The present focus on vaccination, however, has turned to OspC (46,47,93) and other antigens because they are expressed on Borrelia when it enters the human host. Again, epitopes that elicit broad protection without inducing arthritis are prime targets for a vaccine.…”
Section: Arthritis Development In the Absence Of B Burgdorferimentioning
confidence: 99%